The Economics of Islamic Finance and Securitization - Jobst, Andreas (Washington, D.C. : International Monetary Fund, 2007)
Islamic lending transactions are governed by the precepts of the shariah, which bans interest and stipulates that income must be derived as return from entrepreneurial investment. Since Islamic finance is predicated on asset backing and specific credit participation in identified business risk, structuring shariah-compliant securitization seems straightforward. This paper explains the fundamental legal principles of Islamic finance, which includes the presentation of a valuation model that helps distil the essential economic characteristics of shariah-compliant synthetication of conventional finance. In addition to a brief review of the current state of market development, the examination of pertinent legal and economic implications of shariah compliance on the configuration of securitization transactions informs a discussion of the most salient benefits and drawbacks of Islamic securitization.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet